Simulasi Distribusi Tegangan Kanvas Rem Cakram Dengan Geometri Permukaan Yang Baru Untuk Sepeda Motor Standar - Kurniawan, Anggi; Badri, Muftil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In this research refers to the variation of the surface geometry design of the motorcycle disc brake pads. The purpose of this study was to obtain the surface geometry of the disc brake pads and obtain the stress distribution from the surface geometry of the standard motorcycle disc brake pads. In this study was analyzed the stress that occurs on the surface of the disc brake pads. The results of the disc brake pads analysis in the study was evaluated and compared with commercial brake pads products. In the design of surface geometry of motorcycle disc brake pads using geometry modeling software (design modeler) on ANSYS release 12.1. The designs made in this study were varied in 6 designs that being compared and selected from the design, which having the highest stress distribution value. From the simulation result, it was found that having the highest stress distribution value disc brake pads surface geometry for standard motorcycle was on brake pads design 4, which can increase the tension on the surface of the disc brake pads with maximum equivalent stress value of 4.2186 MPa and its minimum value of 0.019341 MPa.Keywords: Geometry surface, disc brake pads, stress distribution, ANSYS simulation.